Improving efficacy of landscape interventions in the (sub) humid Ethiopian highlands by improved understanding of runoff processes - Tebebu, Tigist Y.; Steenhuis, Tammo S.; Dagnew, Dessalegn C.; Guzman, Christian D.; Bayabil, Haimanote K.; Zegeye, Assefa D.; Collick, Amy S.; Langan, Simon; MacAlister, Charlotte; Langendoen, Eddy J.; Yitaferu, Birru; Tilahun, Seifu A. (Frontiers in Earth Science, 2015)
Despite millions of dollars invested in soil and water conservation practices in the (sub) humid Ethiopian highlands and billions of hours of food-for-work farm labor, sediment concentration in rivers is increasing. This paper reports on the research to reverse the current trend. Based on the understanding of the hydrology of highlands, we provide evidence on sources of surface runoff and sediment and on mechanisms that govern the erosion processes and approaches and how they affect soil and water conservation practices. We suggest that priority in landscape interventions should be given to re-vegetation of the degraded areas so as to reduce the sediment concentration contributions originating from these areas. Additionally, efforts should be directed to gully rehabilitation in the saturated bottom landscape that may consist of vegetating shallow gullies and stabilizing head cuts of deeper gullies Finally, rehabilitation efforts should be directed to increase the rain water infiltration in the upland areas through the hard pan layer by connecting the land surface to the original deep flow paths that exist below about 60 cm. It will reduce the direct runoff during the rainy season and increase baseflow during the dry season.